Calopogonium mucunoides, um modelo de estudo para estresses abióticos em climas tropicais - Camargos, Liliane Santos de [UNESP] (My University, 2018)
Calopogonium mucunoides is a tropical herbaceous legume whose adaptive capacity low fertility and high acidic soils motivated the beginning of our research, yet during the PhD. After 2007, several works conducted by us resulted in the identification of some aspects of the biological fixation and the nitrogen metabolism of this species in the presence of N-mineral, as well as the tolerance of its symbiotic system to the presence of nitrate and ammonium, its capacity to fix N at different pH ranges, ranging from acid to near neutrality and, yet, its tolerance to potentially toxic elements. Therefore, it is expected to show an overview of the advances obtained about nitrogen metabolism studies in Calopogonium mucunoides and the future perspectives based on metabolic characterization of this species that may open for new approaches and applications.

Calopogonium mucunoides é uma leguminosa herbácea tropical, cuja capacidade adaptativa a solos de baixa fertilidade e elevada acidez motivou o início de nossas pesquisas, ainda durante o Doutorado. Após 2007, diversos trabalhos por nós conduzidos, resultaram na identificação de alguns aspectos da fixação biológica e do metabolismo de nitrogênio desta espécie na presença de N-mineral, bem como a tolerância de seu sistema simbiótico à presença de nitrato e amônio, sua capacidade de fixação de nitrogênio em diferentes faixas de pH, variando do ácido ao próximo da neutralidade, e, ainda, sua tolerância a elementos potencialmente tóxicos. Com isto, espera-se mostrar um panorama geral dos avanços obtidos no estudo do metabolismo de nitrogênio em Calopogonium mucunoides e as perspectivas futuras que a caracterização metabólica desta espécie pode abrir para novas abordagens e aplicações.
Calopogonium mucunoides, a study model for abiotic stresses in tropical climates
Keywords: Nitrate; Ureides; Nitrogenase; Nitrate reductase; Tolerance; Nitrato; Ureídeos; Nitrogenase; Nitrato redutase; Tolerância